230 Hypophosphatemia: A Risk Factor for Insulin Requirement in Elbw Infants?. (October 2012) - Dreyfus, L; Fischer, CJ; Maucort-Boulch, D; Owono, M Essomo Megnier Mbo; Laborie, S; Claris, O
Abstract : Background and aims: Insulin is frequently required to treat hyperglycemia that increases both mortality and morbidity in ELBW infants. Adult and animal studies suggest a link between hypophosphatemia and insulin resistance. Our objective was to define whether hypophosphatemia increases the risk of insulin requirement in ELBW infants. Methods: This observational study included ELBW infants admitted in our NICU between 01.01.2010 and 31.12.2011 who survived until DOL14. Laboratory and clinical data were retrospectively collected. According to the NICU policy, phosphatemia was measured before DOL3 and glycemia was checked daily during parenteral nutrition. Insulin was introduced in case of refractory hyperglycemia >11mmol/l. Depending on the lowest phosphatemia before DOL3, patients were divided into hypophosphatemic (HP, < 1.2 mmol/l) and controls (≥1.2 mmol/l). Uni- and multivariable analysis compared the time to insulin requirement using survival models. Results: In all, 126 patients were included: 39 HP, 87 controls. Mean(SD) gestational age was 27.8 (1.5) in HP and 27.4 (1.5) weeks in controls, birthweight was 770 (140) and 837 (109) grams. Insulin was required in 19/39 (49%) HP and 26/87 (30%) controls with a delay of 17 (10) and 22 (9) days respectively. The unadjusted hazard ratio of insulin requirement in HP was 1.93 (95%CI: 1.07–3.49, p=0.03). After adjustment for gestational age, birthweight, sex, IUGR and sepsis, the hazard ratio was still 1.6 (95%CI: 0.86–3.17) but not significant (p=0.13) . Conclusion: Hypophosphatemia may be a risk factor for insulin requirement in ELBW. Multivariable analysis shows that age and birthweight could also influence this outcome. Whether aggressive management of hypophosphatemia can improve glycemia control deserves to be studied.